Winter - Marsden, John, 1950- (Sydney : Pan Macmillan, 2001)
Orphaned at four years old, Australian sixteen-year-old Winter de Salis returns to her childhood home in an attempt to find out about her dead parents and her own past.
Keywords: Orphans -- Fiction; Australia -- Fiction